Taxi Time and Energy Plotting Python Program - Pang, Chi Hin (Cranfield University, 2023)
This program runs with Python. By retrieving files created by the Taxi Time and Energy Analysis Program, the program enables users to choose the graph and plot they required.
Keywords: Python'; 'Plot'; 'Graph'; 'E-taxi'; 'Aircraft taxi'